A Construction Method for Personalized Bra Sample Models (Journal of Fiber Bioengineering and Informatics, 2024)
As a close-fitting clothing for women, bras are in direct contact with women’s breasts and fully fit.The bra structure design based on the difference between upper and lower busts cannot meet individualdifferences. To solve the problem that traditional large-scale bra production methods cannot meet theindividual needs of consumers For this problem, a parametric design method for one-person-one-versionpersonalized bra samples is proposed. By analyzing the morphological characteristics of different breastshapes and the composition factors of bra samples, the breast is regarded as a combined model ofellipsoid and cone. The geometric model of breast shape is established, and the model is analyzedby surface flattening technology, and then the breast is obtained. Mathematical representation ofbreast characteristic structure lines include root circumference, surface arc length, and lower teat cuparc. According to the relationship between the breast and the size of the bra sample, the parametricrelationship model of the bra sample is obtained, and the knowledge model of the bra sample isconstructed based on the relationship model, which provides a method for realizing the personalizationof the bra sample.
Keywords: Bra personalization; Geometric model; Parametric relational model; Template knowledge model